National Factors of Cluster Development and Management - Hvižďáková, Ivana (Észak-magyarországi Stratégiai Füzetek, 2013)
The changing environment puts pressure on performance of business. In order to stay competitive firms create clusters, which require a more collaborative management; collaborative in the sense of creating relationships and trust, working on mutual investment and innovation projects and looking for ways to finance this change. The factors, which influence cluster development and also management, may come from the micro as well as the macro level. The aim of the article is to study the impact of national factors on cluster development and management in the EU countries. The results of analysis suggest that social capital dimensions have a differing influence on the proportion of clusters in an economy, while the level of innovation performance has a positive influence.